PrEP (non-)adherence among men who have sex with men in Portugal: A qualitative study - Pinheiro, G. G.; Moleiro, C.; Rodrigues, D. L. (18th Congress of the European Federation of Sexology, 2026)
Objective: Portugal is among the Western European countries with the highest rates of new HIV diagnoses. Despite pre-exposure prophylaxis (PrEP) efficacy in reducing HIV transmission, adherence rates remain below UNAIDS targets, even among key populations. We conducted a qualitative study with men who have sex with men (MSM) living in Portugal, including both PrEP users and non-users, to explore perceptions of oral PrEP using the PrEP care continuum framework. Design and Method: We conducted 17 semi-structured interviews. The interview script included openended questions addressing three main domains: (1) advantages and disadvantages of PrEP use; (2) social perceptions towards PrEP users; and (3) relations with the healthcare system. Data was subject to content analysis and incorporated features of consensual qualitative research to ensure rigorous systematic coding, team consensus, and validation of interpretations. Results: Findings highlighted the role of the community in raising PrEP awareness and uptake, including community-based services and peer networks. However, the limited availability of community-based services outside major urban centers created barriers for individuals living in rural areas, where PrEP stigma was more salient, particularly among those with intersecting marginalized identities, such as migrant individuals. Stigma hindered PrEP promotion, affecting users’ sexual and romantic interactions, as it was associated with promiscuity or perceived as intended only for cis-MSM. A perception reported either by cis and trans MSM in our sample. Moreover, a high perception of HIV risk emerged as a key factor driving PrEP awareness, uptake, and adherence. In contrast, a low perception of risk was associated with reduced willingness to use PrEP and PrEP discontinuation. Conclusions: By contextualizing PrEP within the Portuguese healthcare landscape, this study contributes to filling an important gap in our understanding of PrEP awareness, uptake, and adherence among MSM in Portugal, and offers valuable insights that can inform public health policy and practice during a critical transitioning period with the expansion of PrEP through the primary healthcare system.